Analisis Pesepsi dan Preferensi di Embung A Sebagai Komponen Pengelolaan Embung di Institut Teknologi Sumatera - Rizka Nabilah; Rian Adetiya Pratiwi; Cipta Vidyana (Jurnal Lanskap Indonesia, 2019)
Institut Teknologi Sumatera (ITERA) has artificial lake reservoirs, it’s called embung. This embung needs landscape management for conservation water resources. Embung which is have functions as a water reserves to anticipate in the dry season and problem run off in the rainy season. Embung A ITERA has a plan and design. So, it is important for the next activity, which is the management landscape of embung. This management process is related to the coordination concepts of the embung landscape, visitors and policy makers in ITERA. Embung landscape management is needed as a part of the physical maintenance and ideal maintenance of the embung. The purpose of this study is to compose lake management recommendations as a sustainable blue open space in ITERA. The data obtained perception data on the response of the existing reservoir management. The questionnaire will be directed to find out how visitors care about the management of the embung A ITERA. Statistical data analysis was performed based on Pearson correlation analysis. The results showed 82.2% of visitors understanding of landscape management was related to the policy analysis and perceptions of the embung visitors with a value of 80.6%. From the data showed that the management link with the highest value is maintaining the cleanliness of the embung A ITERA environment which is the perception of visitors with a value of 0.95 (positive).